ANO5 Gene Analysis in a Large Cohort of Patients with Anoctaminopathy: Confirmation of Male Prevalence and High Occurrence of the Common Exon 5 Gene Mutation. Issue 8 (12th June 2013) - Sarkozy, Anna; Hicks, Debbie; Hudson, Judith; Laval, Steve H.; Barresi, Rita; Hilton‐Jones, David; Deschauer, Marcus; Harris, Elizabeth; Rufibach, Laura; Hwang, Esther; Bashir, Rumaisa; Walter, Maggie C.; et al.
ABSTRACT Limb girdle muscular dystrophy type 2L or anoctaminopathy is a condition mainly characterized by adult onset proximal lower limb muscular weakness and raised CK values, due to recessive ANO5 gene mutations. An exon 5 founder mutation (c.191dupA) has been identified in most of the British and German LGMD2L patients so far reported. We aimed to further investigate the prevalence and spectrum of ANO5 gene mutations and related clinical phenotypes, by screening 205 undiagnosed patients referred to our molecular service with a clinical suspicion of anoctaminopathy. A total of 42 unrelated patients had two ANO5 mutations (21%), whereas 14 carried a single change. We identified 34 pathogenic changes, 15 of which are novel. The c.191dupA mutation represents 61% of mutated alleles and appears to be less prevalent in non‐Northern European populations. Retrospective clinical analysis corroborates the prevalently proximal lower limb phenotype, the male predominance and absence of major cardiac or respiratory involvement. Identification of cases with isolated hyperCKaemia and very late symptomatic male and female subjects confirms the extension of the phenotypic spectrum of the disease. Anoctaminopathy appears to be one of the most common adult muscular dystrophies in Northern Europe, with a prevalence of about 20%–25% in unselected undiagnosed cases.